Role of nasal carriage of Staphylococcus aureus in chronic urticaria - Ashimav Deb Sharma (Wolters Kluwer Medknow Publications, 2012)
Aim: To evaluate the role of nasal carriage of Staphylococcus aureus in patients suffering from chronic urticaria. Method: All total 82 patients were included for this study. Study group comprised 57 patients with chronic urticaria and the control group comprised 25 healthy volunteers. Nasal swab specimens were taken from all the 82 patients for bacterial culture and antimicrobial sensitivity. Patients with chronic urticaria who had positive growth for S. aureus were treated with sensitive antimicrobial agent. Nasal swab specimens were taken again from all the patients who received antimicrobial therapy to ensure complete eradication of S. aureus. All patients were followed up for a period of 6 weeks after the treatment. Urticarial activity was measured with the help of urticarial activity score. Results: S. aureus was detected in swab specimens from the nasal cavity in 32 patients in the study group and 7 patients in the control group. In the study group, after the antimicrobial treatment, 9 patients (28.12%) had complete recovery from urticaria during the follow-up period; 4 patients (12.5%) showed partial recovery from urticaria while the remaining patients (59.37%) continued to suffer from urticaria. Conclusion: This study showed that nasal carriage of S. aureus can act as an etiological factor in chronic urticaria.